30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-2914
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Impacts of Helicopter Blade Erosion Coatings

Abstract: The United States Army helicopter fleet experiences deformation of rotor blade contours from sand erosion and the implementation of technologies to protect against it. An investigation was performed to determine the effect of a typical erosion protection coating on the main rotor performance of a UH-60A Blackhawk utility helicopter. Computational fluid dynamics was used to calculate aerodynamic coefficients for representative coated airfoil sections. Hover analyses were performed to evaluate the impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This mimics the use of protective leading edge tapes or coatings used for helicopter and wind turbine blades. Protective tapes without the serration have previously been studied and shown to protect the rotor blades while significantly increasing the profile drag [22]. Qualitative investigations adding the serration suggested that it could mitigate the added drag.…”
Section: Introductionmentioning
confidence: 99%
“…This mimics the use of protective leading edge tapes or coatings used for helicopter and wind turbine blades. Protective tapes without the serration have previously been studied and shown to protect the rotor blades while significantly increasing the profile drag [22]. Qualitative investigations adding the serration suggested that it could mitigate the added drag.…”
Section: Introductionmentioning
confidence: 99%
“…The blades make pitch movements around the longitudinal axis, forward-backward movement within the rotational plane, and flutter up and down perpendicular to the rotational plane. Therefore, the helicopter has high maneuverability and a good control response [ 21 ]. The shaft is positioned in the upper part of the body in order that the center of gravity is in line with the vertical axis.…”
Section: The Selection and Design Of Subsystemsmentioning
confidence: 99%
“…The area of coatings and materials is an active research avenue in itself, and sacrificial coatings seem to be the norm. Calvert et al [3] have shown that the application of sacrificial erosion as well. This is one of the most successful models that has been used along with the Wilcox roughness model (discussed later) for turbomachinery applications.…”
Section: Introductionmentioning
confidence: 98%